Trafficking Dynamics of PCSK9-Induced LDLR Degradation: Focus on Human PCSK9 Mutations and C-Terminal Domain - Poirier, Steve (PLoS One, 2016)
PCSK9 is a secreted ligand and negative post-translational regulator of low-density lipoprotein receptor (LDLR) in hepatocytes. Gain-of-function (GOF) or loss-of-function (LOF) mutations in PCSK9 are directly correlated with high or low plasma LDL-cholesterol levels, respectively. Therefore, PCSK9 is a prevailing lipid-lowering target to prevent coronary heart diseases and stroke. Herein, we fused monomeric fluorescent proteins to PCSK9 and LDLR to visualize their intra- and extracellular trafficking dynamics by live confocal microscopy. Fluorescence recovery after photobleaching (FRAP) showed that PCSK9 LOF R46L mutant and GOF mutations S127R and D129G, but not the LDLR high-affinity mutant D374Y, significantly accelerate PCSK9 exit from the endoplasmic reticulum (ER). Quantitative analysis of inverse FRAP revealed that only R46L presented a much slower trafficking from the trans-Golgi network (TGN) to the plasma membrane and a lower mobile fraction likely suggesting accumulation or delayed exit at the TGN as an underlying mechanism. While not primarily involved in LDLR binding, PCSK9 C-terminal domain (CTD) was found to be essential to induce LDLR degradation both upon its overexpression in cells or via the extracellular pathway. Our data revealed that PCSK9 CTD is required for the localization of PCSK9 at the TGN and increases its LDLR-mediated endocytosis. Interestingly, intracellular lysosomal targeting of PCSK9-ΔCTD was able to rescue its capacity to induce LDLR degradation emphasizing a role of the CTD in the sorting of PCSK9-LDLR complex towards late endocytic compartments. Finally, we validated our dual fluorescence system as a cell based-assay by preventing PCSK9 internalization using a PCSK9-LDLR blocking antibody, which may be expended to identify protein, peptide or small molecule inhibitors of PCSK9.